2005
DOI: 10.1002/pola.20774
|View full text |Cite
|
Sign up to set email alerts
|

Photocycloaddition‐induced preparation of nanostructured, cyclic polymers using biscinnamated or biscoumarinated oligo(ethylene glycol)s

Abstract: Two types of photoreactive water‐soluble oligo(ethylene glycol)s (OEGs; Mn = ca. 6500) were prepared by derivatization of OEG with photodimerizable groups such as cinnamates or coumarinates at both ends. Upon UV light irradiation of biscinnamated OEG in an aqueous solution, almost all trans‐cinnamate groups were isomerized to cis form in preference to dimerization even in an associated state at high concentrations of cinnamate groups, whereas dimerization via intermolecular photocycloaddition was the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…Though their dimer has no absorption peak between 250 and 350 nm, both the trans-and cis-monomers have an absorption peak at 280 nm. [34,35] When only trans-cis isomerization proceeds, an isosbestic point appears at 250 nm. As shown in Figure S3, Supporting Information, the disappearance of the isosbestic point in the PCEMA-g-PDMS spectra demonstrates that the cinnamoyl groups of PCEMA-g-PDMS undergo dimerization with isomerization under UV exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Though their dimer has no absorption peak between 250 and 350 nm, both the trans-and cis-monomers have an absorption peak at 280 nm. [34,35] When only trans-cis isomerization proceeds, an isosbestic point appears at 250 nm. As shown in Figure S3, Supporting Information, the disappearance of the isosbestic point in the PCEMA-g-PDMS spectra demonstrates that the cinnamoyl groups of PCEMA-g-PDMS undergo dimerization with isomerization under UV exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the chain growth polymerization systems, photo‐induced step growth polymerizations are also emerging as an increasingly attractive topic in polymer synthesis. Various photoreactions or photoinduced reactions, such as thiol‐ene reaction,9 photodimerization of cinnamates or coumarinates,10 photodimerization of 2‐furanacrylates,11 photoinduced electron transfer of iodonium salt,12 light induced nitrile imine‐mediated tetrazole‐ene cycloaddition (NITEC),13 UV‐light induced Diels–Alder reaction,14 etc., have been used for step growth polymerizations. In addition, AB‐type of monomers possessing aliphatic hydroxyl and photo labile benzodioxinones (as masked COOH) was also used for the synthesis of oligo polyester as a demonstration of the concept of photo induced step growth polymerization 15.…”
Section: Reaction Conditions and Results Of The Polymerizations Throumentioning
confidence: 99%
“…If the trans-cis isomerization solely proceeds, an isosbestic point appears at 250 nm. 21 The disappearance of the isosbestic point in the spectra clearly showed that dimerization competes with isomerization in the sample during photoirradiation (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%